Universities at War - Newcastle University (2022)
"Welcome to Universities at War. This is a collaborative HLF-funded First World War project led by Newcastle and Durham Universities in which volunteers research and tell the stories of the fallen associated with both institutions (then united within a larger University of Durham), whether students, alumni, or staff. At the time of the First World War the university and its associated colleges comprised an unusual group of technical and professional institutions, with a strong local student and alumni body, and more traditional colleges, with a wider national and international population. Universities at War therefore offers a view of the lives of an unusual group of men from all over the country and across diverse socio-economic groups." [slf-cdescription]